1991
DOI: 10.1007/bf00918792
|View full text |Cite
|
Sign up to set email alerts
|

Expression and functions of very late antigen 1 in inflammatory joint diseases

Abstract: In the human immune system, very late antigen 1 (VLA-1), a putative collagen receptor, is expressed on the surface of T lymphocytes that have undergone mitogenic or antigenic stimulation. A new VLA-1-specific monoclonal antibody, 1B3.1, was used to probe the expression and function of VLA-1 on T lymphocytes in patients with arthritis. Synovial mononuclear cells from the joints of patients with rheumatoid arthritis or other joint diseases contained 32.9 +/- 13.8% 1B3.1-positive cells (42.8 +/- 10.4% in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 23 publications
2
23
0
Order By: Relevance
“…Consistent with the initial description of ␣ 1 ␤ 1 and ␣ 2 ␤ 1 as VLAs, expression of these integrins has been described as being induced in vitro on long-term activated T cells and in vivo on infiltrating T cells in chronic inflammatory settings (4,8,9,(11)(12)(13). Given the importance of collagen-integrin interactions in modulating effector inflammatory responses in vivo and in affecting T cell function in vitro (2, 3), we sought to investigate the expression and function of ␣ 1 ␤ 1 and ␣ 2 ␤ 1 integrins on virus-activated T cells.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Consistent with the initial description of ␣ 1 ␤ 1 and ␣ 2 ␤ 1 as VLAs, expression of these integrins has been described as being induced in vitro on long-term activated T cells and in vivo on infiltrating T cells in chronic inflammatory settings (4,8,9,(11)(12)(13). Given the importance of collagen-integrin interactions in modulating effector inflammatory responses in vivo and in affecting T cell function in vitro (2, 3), we sought to investigate the expression and function of ␣ 1 ␤ 1 and ␣ 2 ␤ 1 integrins on virus-activated T cells.…”
Section: Discussionmentioning
confidence: 62%
“…In addition, it has been found that certain viral infections may induce T cell expression of DX5, which following completion of this study has been revealed to be ␣ 2 ␤ 1 ϩ (DX5 ϩ ) (8 -10). Also, infiltrating T cells from different chronic inflammatory exudates have been found to express ␣ 1 ␤ 1 (2,(11)(12)(13). Most information regarding the role of ␣ 1 ␤ 1 and ␣ 2 ␤ 1 as receptors for collagen has been obtained through in vitro adhesion and migration assays on collagen matrices (14,15).…”
mentioning
confidence: 99%
“…Because VLA-1 is expressed only on T lymphocytes that have undergone stimulation (Bank et al, 1991), to further investigate the promoting role of VLA-1 in the development of the secondary lesion, we used T cells isolated from peripheral DLN of arthritic rats. In vitro stimulation of DLN T cells isolated from FA rats with ConA caused a significant increase in labeled thymidine uptake when compared with DLN T cells isolated from naive rats.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that activated T lymphocytes express on their surface a group of high molecular weight proteins called integrins constituted by noncovalent linked ␣␤ heterodimeric subunits of 95-200 kDa. One member of this family, very late antigen (VLA)-1, has been shown to act as a cell surface receptor for collagen and laminin and to be expressed on activated T cells in vitro and in vivo (Bank et al, 1991;Hemler et al, 1985). VLA-1 (␣1␤1 integrin) is one of two major collagen/laminin binding integrins, and its expression is up-regulated in persistently activated, cultured (2-4 weeks) T cells (Hemler et al, 1986 ) and rapidly induced on the monocyte cell surfaces by lipopolysaccharide or ␥-interferon (Rubio et al, 1995).…”
mentioning
confidence: 99%
“…Furthermore, VLA-1/collagen interactions augment T cell receptor-mediated (TCR-mediated) proliferation and cytokine secretion (12,13). Importantly, recent studies in murine models of inflammation show that deleting the α1 integrin gene or blocking the functions of VLA-1 in vivo with mAb's prevents the development of delayed-type hypersensitivity-like (DTHlike) immune responses, including those associated with graft-versus-host disease, adjuvant or Abinduced arthritis, and hapten-induced colitis (14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%